1902
DOI: 10.1086/328303
|View full text |Cite
|
Sign up to set email alerts
|

A Morphological Study of Certain Asclepiadaceae

Abstract: IN a previous paper (7) the results of a study of the pollen of certain Asclepiadaceae were published, and during that investigation the remarkable structure of some of the floral organs attracted attention. The present paper is the result of their study. The species studied were Asclepias Cornulti Dec., A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
1

Year Published

1925
1925
1995
1995

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 0 publications
3
21
0
1
Order By: Relevance
“…Isolated tracheids not connected to the vascular supply in the funiculus are reported for Castanea (Benson, 1894), Carpinus (Benson, Sandy, and Berridge, 1906), and for Asclepias (Frye, 1902). The widespread occurrence among unrelated taxa of vascular elements centrally located in these axes once again supports derivation of the nucellus from a fertile telome.…”
Section: Origin Of the Ovule: A New Conceptmentioning
confidence: 87%
“…Isolated tracheids not connected to the vascular supply in the funiculus are reported for Castanea (Benson, 1894), Carpinus (Benson, Sandy, and Berridge, 1906), and for Asclepias (Frye, 1902). The widespread occurrence among unrelated taxa of vascular elements centrally located in these axes once again supports derivation of the nucellus from a fertile telome.…”
Section: Origin Of the Ovule: A New Conceptmentioning
confidence: 87%
“…Frye (1902) observed that in the mature flower there are from one to six in each group, the number and size varying even in the same flower. Usually, colleters are side by side on the organ to which they are attached, but sometimes they are placed radially.…”
Section: Taxonomic Considerationsmentioning
confidence: 93%
“…Rev effected when a pollinium lodges in a stigmatic chamber (79). Pollen tubes subsequently grow down the stylar canal and finally enter the ovary (17,25). Pollen tubes subsequently grow down the stylar canal and finally enter the ovary (17,25).…”
Section: Floral Morphology and Anatomymentioning
confidence: 99%